2005
DOI: 10.1007/s00278-005-0438-x
|View full text |Cite
|
Sign up to set email alerts
|

Indikation zur ambulanten Nachsorge (Curriculum Hannover) in der Psychosomatischen Rehabilitation

Abstract: belt · Eber hard Grosch · LVA Han no ver, Ärzt li cher DienstIn di ka ti on zur am bu lan ten Nach sor ge (Cur ri cu lum Han no ver) in der Psy chosoma ti schen Re ha bi li ta ti on Viel e Men schen, die eine me di zi nischpsy cho so ma ti sche Re ha bi li ta ti ons be handlung durch lau fen, wa ren bis her da rauf an ge wie sen, sich an der Schnitt stel le zwischen sta tio närer Re ha bi li ta ti ons be handlung und meist un ver än dert ge blie be nem All tag zu recht zu fin den. Die seit 2000 bundes weit an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 1 publication
0
8
0
4
Order By: Relevance
“…In medical internet research, it has been shown that outpatient psychotherapeutic treatment after rehabilitation treatment is an important factor in ensuring the sustainability of treatment effects [1][2][3][4][5][6][7][8][9]24,25]. At the same time, research has demonstrated the benefits of online psychotherapy in comparison with F2F psychotherapy on site [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In medical internet research, it has been shown that outpatient psychotherapeutic treatment after rehabilitation treatment is an important factor in ensuring the sustainability of treatment effects [1][2][3][4][5][6][7][8][9]24,25]. At the same time, research has demonstrated the benefits of online psychotherapy in comparison with F2F psychotherapy on site [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, so far, no study can be found addressing the comparison of the same aftercare delivered online (content and procedure of the therapy; Curriculum Hannover [ 24 , 25 ]) with F2F and CAU in terms of study dropout and intervention withdrawal. Thus, this was the main aim of this study, since the usefulness of Curriculum Hannover was tested before and clearly revealed its superiority to CAU, as well as parity between the internet and F2F delivery modes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation that needs to be considered is that the digital trainings offered before and during the rehabilitation stay so far have not been validated or standardized, but rather align with the German regulations for rehabilitation treatments and were developed based on experiences by the rehabilitation clinics. Hence, with regard to future research, a standardized manual, such as the Curriculum Hannover for aftercare [55], should be developed to effectively integrate standardized and evaluated digital trainings into the rehabilitation treatment process. In Germany, a cultural particularity of rehabilitation is that rehabilitation is mostly done in in-patient settings and has to be applied for with pension insurance funds by insured persons.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…Another limitation that needs to be considered is that the digital trainings offered before and during the rehabilitation stay so far have not been validated or standardized but rather align with the German regulations for rehabilitation treatments as well as being developed based on experiences by the rehabilitation clinics. Hence, with regard to future research a standardized manual, such as Curriculum Hannover for aftercare [52], should be developed to effectively integrate standardized and evaluated digital trainings into the rehabilitation treatment process.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%